Urban atmospheres of terror. (June 2022) - Fregonese, Sara; Laketa, Sunčana
Abstract: This essay advances an affective agenda in urban geopolitics that studies the everyday felt experience of urban terrorism. It takes as examples the relations between the spatial politics and affective atmospheres of Place de la République (Paris) and Place de la Bourse/Beursplein (Brussels) in the aftermath of the terrorist attacks of 2015 and 2016. Intersecting feminist geopolitics and non-representational geographies, the essay bridges geographical studies of experience and affective atmospheres with experiential accounts in urban geopolitics. It argues for a renewed conceptual engagement and scholarly focus on the affective dimensions of urban geopolitics and security, that highlights the contested and unequal topographies of everyday experience in the aftermath of terrorism in urban Europe.